Entomopathogenic Nematodes: The Parasites Useful for Biological Control Strategy - Pokhrel, Narayan (Tribhuvan University Journal, 2011)
Not available. Key words: Entomopathogenic; Biological Control Strategy; Molluska Tribhuvan University Journal Vol. 21, No.2, 1998 Page:95-101 Uploaded Date: 9 May, 2011